Association between heavy metal exposure and bacterial vaginosis: A cross-sectional study - Yu-Xue Feng; Ming-Zhi Tan; Hui-Han Qiu; Jie-Rong Chen; Si-Zhe Wang; Ze-Min Huang; Xu-Guang Guo (PLoS ONE, 2025)
Bacterial vaginosis (BV) is a prevalent cause of vaginal symptoms in women of reproductive age. With the widespread of heavy metal pollutants and their harmful function on women’s immune and hormonal systems, it is necessary to explore the association between heavy metal exposure and BV. This study investigates the potential relationship between serum heavy metals and bacterial vaginosis in a cohort of American women. The present study employed a cross-sectional analysis of 2,493 women participating in the 2001–2004 National Health and Nutrition Examination Survey (NHANES). Multivariable logistic regression models were utilized in the study to assess the correlation between these variables. A stratified analysis was performed to investigate the relationship among different population groups further, and smooth curve fittings were conducted to intuitively evaluate the correlation. According to the current cross-sectional study results, a significant correlation was identified between the high levels of lead and cadmium in the serum and the likelihood of developing bacterial vaginosis. We found that serum lead (OR = 1.35, 95% CI: 1.06–1.72, p = 0.016) and serum cadmium (OR = 1.41, 95% CI: 1.01–1.98, p = 0.047) increased the risk of bacterial vaginosis by 35% and 41%, respectively, in the highest level group in comparison to the lowest level group in the fully adjusted model. Furthermore, the research discovered no statistically significant association between the levels of total mercury in the serum and a heightened susceptibility to bacterial vaginosis (OR = 0.96, 95% CI: 0.75–1.23, p = 0.763). Results of our study indicated an inverse association between serum heavy metals and bacterial vaginosis risk, including lead and cadmium. Reducing exposure to heavy metals could be vital to preventing and managing bacterial vaginosis.